Biochemical characterization of Xanthomonas oryzae pv. oryzae isolates collected from Telangana and Andhra Pradesh - Padmaja, Gunjan; Devi, G Uma; Yugander, A; Srinivas, C; Rani, Ch V Durga; Sundaram, R M; Laha, G S (Indian Journal of Plant Protection, 2020)
Bacterial blight (BB) of rice caused by Xanthomonas oryzae pv. oryzae (Xoo) is a serious problem in rice production in India especially in irrigated and rainfed lowland ecosystem. BB has become a serious problem in several rice growing areas of Telangana and Andhra Pradesh. Sixty Xoo isolates collected from different rice growing regions of Telangana and Andhra Pradesh were characterized for their reaction to different biochemical tests. Xoo isolates were gram negative, showed positive reaction for H2S production, catalase production, gelatin liquefaction and produced acid from several carbohydrates but not from alanine. The Xoo isolates showed a negative reaction for oxidase, urease production and indole production. Xoo isolates showed variable reactions with respect to lecithinase, nitrate reduction, starch hydrolysis and acid production from inositol. The results indicate that there exists variation in physiological characters among the Xoo isolates and this may have impact on their virulence and survival.